Assessing the robustness of the relationship between financial reforms and banking crises - Gluzmann, Pablo Alfredo (2017)
This paper provides a novel approach for assessing the robustness of the relationship between different types of financial reforms and banking crises for the period 1973– 2005. We document the following facts for emerging economies: (i) liberalizations of capital accounts, securities markets, interest rates, removal of credit controls, barriers to entry, and reduction of state ownership in the banking sector, all are positively associated with a higher frequency of banking crises; (ii) the increase in financial turbulence is mainly concentrated within a time-window of five years after the reforms: If a country does not experience a banking crisis within that period, the probability of experiencing a crisis afterwards becomes insignificant; and (iii) the results are robust to the inclusion of all control variables that have been found in the literature as significant determinants of banking crises.